GAME METHODS AS A MEANS OF LEARNING A FOREIGN LANGUAGE - Волошина, Оксана; Попенко, Юлия (SWorldJournal, 2020)
The article deals with the problems of learning a foreign language, examines the correct selection of methods by which students will better learn everything, and through which games can learn foreign language faster and more thoroughly.